Can information help reduce imbalanced application of fertilisers in India: Experimental evidence from Bihar - Fishman, Ram; Kishore, Avinash; Rothler, Yoav; Ward, Patrick S.; Singh, R. K. P.; Jha, Shankar (International Growth Centre, 2019)
The imbalanced application of different types of chemical fertilisers in agriculture is a widespread problem in India. This imbalance affects soil fertility, crop productivity and farmers’ net profits, and results in widespread pollution of water resources. In this context, the Government of India has launched the Soil Health Cards (SHC) programme to promote the balanced use of fertilisers in agriculture throughout India. More than 140 million SHCs are expected to be issued for 3 years to cover all plots and farmers in India. The programme aims to provide custom scientific information, which will encourage farmers to opt for a more balanced use of fertilisers. Under this programme, all farmers in India will receive the details over the nutritional status of their land and crop-wise yield specific recommendations for the application of different fertilisers. States like Gujarat have already implemented a similar programme where farmers received crop-specific fertiliser application recommendations for all plots of land with plot-level SHC information posted on the website. On the other hand, Bihar remains a laggard state in issuing SHC to its farmers. However, this programme is based on certain implicit assumptions. First, it assumes that smallholder farmers, many of whom are illiterate, will be able to understand the contents of SHC. Second, even if farmers understand the content, the assumption is that they will trust the quality and reliability of the information. Third, farmers will alter their preferred use of fertilisers based on the information of the SHC. Finally, the farmers will be able to act on their altered preference without being constrained by other factors that may affect their choices.